Optimizing DC alloy properties: Impact of T6 heat treatment at high solution temperatures on β-AlFeSi phase transformation - Mohamad Rusydi, Mohamad Yasin; Muhammad Syamim, Mazlan; Nurul Nadia, Nor Hamran (Springer Singapore, 2024)
Aluminum–Silicon (Al-Si) alloys are widely used in Die-Casting (DC) applications due to their low thermal expansion and excellent mechanical properties. Nevertheless, iron inclusion in the composition is sometimes seen as disadvantageous due to its tendency to create brittle β-AlFeSi phase precipitates, which may result in a decrease in the alloy's ductility. Hence, the regulation of the β-AlFeSi phase is of paramount importance to further improve mechanical characteristics. Heat treatment is a well-recognized technique used to manipulate the shape of the β-AlFeSi intermetallic phase and enhance its properties. This research aims to comprehensively examine the impacts of modified T6 heat treatment on the A380 Al-Si alloy. The heat treatment procedure included manipulating the solution temperature and examining its impact on the microstructure and mechanical characteristics of the alloy. The results of our study indicate that a T6 solution temperature of 515 °C for a short duration is the most effective in dissolving the β-AlFeSi phase and enhancing the elongation of the DC alloy to 3.39%. The observed temperature facilitates the conversion of the β-AlFeSi phase to the α-AlFeSi phase, which is known to have fewer adverse effects on the properties of the alloy. The observed enhancement in elongation, a critical indicator of ductility, indicates that subjecting Al-Si alloys to high-temperature heat treatment might serve as a viable approach for augmenting their mechanical characteristics. The results emphasize the potential efficacy of using high-temperature heat treatment as a feasible approach for enhancing the characteristics of Al-Si alloys.